AN AXIOLOGICAL APPROACH TO MENTAL MAPS: CROATIAN HIGH-SCHOOL STUDENTS' VIEWS OF EUROPE - Laura SAKAJA (European Journal of Geography)
The paper presents the results of a survey carried out in the academic year 2016/2017 and deals with the attitudes of Croatian high-school students towards European countries. This survey repeats an earlier study from 2000/2001 and thus allows a comparison of the opinions of young people from different generations. The data indicate a shift in residential preferences towards the Nordic countries, while preferences towards the Latin/Mediterranean countries have weakened. Applying an axiological approach to the original model of mental maps made it possible to gain insight into the value criteria used to assess the residential desirability of countries. Groups of evaluation criteria were identified, the most important of which being the following: (a) Employment opportunities, economic conditions and economic development; (b) Culture, way of life, cultural landscape; (c) Political and legal order, social security, and freedom; and (d) Ethnopsychological factors.